The existence of kuda lumping performances in terms of character education based on the principles of Pancasila - Dionisius Heckie Puspoko Jati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The present study examines the traditional art of Kuda Lumping through the perspective of character values reflected in the principles of Pancasila. As a traditional Indonesian cultural practice, Kuda Lumping represents a local heritage with aesthetic appeal and deep moral significance relevant to social life. However, its existence faces increasing threats from globalisation and modern lifestyle changes, mainly due to a lack of artist regeneration. Using a qualitative approach with a descriptive-analytical method, data were collected via in-depth interviews with Kuda Lumping artists, community figures, art observers, and elementary school teachers and students, alongside direct observations and a review of relevant literature. The research aims to identify character values within Kuda Lumping that align with Pancasila, analyse factors influencing its sustainability, and explore strategies for its preservation as a medium for cultural and character education. The findings emphasise the importance of maintaining Kuda Lumping as part of the national cultural identity and a tool for fostering Pancasila values, especially among elementary students. The study also proposes strategic recommendations, including arts-based education programmes, digitalising performances, and enhancing support from government and cultural communities. It is hoped that Kuda Lumping will continue to flourish as both a cultural heritage and a means of character development aligned with Pancasila.